Articulating a Rights-based Argument for Mathematics Teaching and Learning in Early Childhood Education. Issue 3 (September 2016) - Cohrssen, Caroline; Page, Jane
MATHEMATICS IS COMMONLY CITED in Australian and international literature as an integral component of quality early childhood education and care (ECEC) programs. This article presents a rights-based argument for early childhood educators to integrate mathematical concepts into daily ECEC practice. There is a lack of educator confidence in the ECEC sector regarding teaching mathematics concepts to preschool-aged children. At the same time, many children from low socioeconomic status backgrounds underperform in mathematics and girls are under-represented in so-called STEM (science, technology, engineering and mathematics) subjects in later schooling. Providing opportunities for young children to participate in mathematical thinking in their daily educational programs provides opportunities for children to develop competencies that will equip them to be active citizens, now and in the future. This is an important means of ensuring equitable learning outcomes for all children.